Estimating Driving Behavior by a Smartphone - Eren, H.; Makinist, S.; Akin, E.; Yilmaz, A. (Ieee, 2012)
In this paper, we propose an approach to understand the driver behavior using smartphone sensors. The aim for analyzing the sensory data acquired using a smartphone is to design a car-independent system which does not need vehicle mounted sensors measuring turn rates, gas consumption or tire pressure. The sensory data utilized in this paper includes the accelerometer, gyroscope and the magnetometer. Using these sensors we obtain position, speed, acceleration, deceleration and deflection angle sensory information and estimate commuting safety by statistically analyzing driver behavior. In contrast to state of the art, this work uses no external sensors, resulting in a cost efficient, simplistic and user-friendly system.
IEEE Intelligent Vehicles Symposium (IV) -- JUN 03-07, 2012 -- Alcala de Henares, SPAIN
Keywords: Driver behavior; accelerometer; gyroscope; magnetometer; smart phone; unsafe driving; Bayesian classification